WHAT KIND OF TEACHERS DOES PRIMARY SCHOOL STUDENTS WANT? (Third Sector Social Economic Review, 2019)
In this study, it is aimed to determine what kind of teacher elementary school students want. Data were collected from 177 primary school students by using semi-structured open-ended questions, both written and verbal. The collected data were analyzed using descriptive and content analysis techniques. As a result of the study: 1) The teacher model that most desired by primary school students is; ”sincere, friendly, jocund, caring, compassionate, affectionate, merciful, happy, humorous, impartial, fair, tolerant, considerate, success seeing (appreciating, rewarding, etc.), and the ones who teach the lesson on time and adequately by using various teaching methods and activities (role playing, using music, paint activities etc.), and who spend time with student…” 2) The most unwanted teacher attitude and behaviors stated by the students were; “angry, grumpy, indifferent, punishing, irresponsible, unfair, unhappy, shouting, using violent, threatening, condescending, intolerant, boring, insulting, rude,  and the ones who guide the students adequately, and teach the lessons in a monotonous way, and giving much homework…”
Keywords: Primary school; student; teacher; expectation; behavior.